THE DIVINITIES OF MOCHIC CULTURE - Lieske, Bärbel (2009)
The present work tries to do a compendium of the representations of the pantheon mochica. The intention was to recognize the divinities with his distinguishable characteristics, to group them, to name them and to present them in chosen images, accompanied by a brief description. Until now a systematical catalog of this nature has not been offered. The work wants to form the base for the handling of the representations numinosas in the art mochica. The images try to show the variety of the divinities and he wants to help in the identification of them. I hope that it induces to later works and to the debate.